2007
DOI: 10.1590/s0066-782x2007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos cardiovasculares da anestesia local com vasoconstritor durante exodontia em coronariopatas

Abstract: SummaryObjective: To evaluate the occurrence of variables detecting myocardial ischemia during or after dental treatment under anesthesia with vasoconstrictor (epinephrine).Methods: vasoconstrictor were included. They were divided into two groups (by drawing envelopes): group I (27 patients) using echocardiogram before and after dental intervention, and determination of biochemical markers (CK-MB mass, CK-MB pressure were also measured in the pre, post-anesthesia and post-dental extraction phases. Doppler echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 10 publications
3
21
1
5
Order By: Relevance
“…Epinephrine is a sympathomimetic catecholamine which is believed to increase (both systolic and diastolic) blood pressure. Research on the effects of epinephrine-containing solutions on blood pressure has reported these solutions to have no particular clinical side effects in healthy people (Conrado et al, 2007;Meral et al, 2005;Degerliyurt & Denizci, 2013;de Morias, de Santanastos, de Costa Araujo, Vajgel, & de Holanda Vascouncellos, 2012;de Morais et al, 2012;Akutsu, Chiba, Takahashi, Shimoda, & Suematsu, 1964).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epinephrine is a sympathomimetic catecholamine which is believed to increase (both systolic and diastolic) blood pressure. Research on the effects of epinephrine-containing solutions on blood pressure has reported these solutions to have no particular clinical side effects in healthy people (Conrado et al, 2007;Meral et al, 2005;Degerliyurt & Denizci, 2013;de Morias, de Santanastos, de Costa Araujo, Vajgel, & de Holanda Vascouncellos, 2012;de Morais et al, 2012;Akutsu, Chiba, Takahashi, Shimoda, & Suematsu, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…In conrado et al study, all were heart failure cases. (Conrado et al, 2007) Elad et al (2008 enrolled patients with controlled hypertension, but did not mentioned the presence of others cardiovascular diseases of their participants. The participants in the present study only had controlled hypertension and no other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of vasoconstrictors should be avoided in patients with high risk of cardiovascular disease and uncontrolled diabetes. In such cases or when emergency procedures are required, it is suggested to opt for 3% prilocaine with felypressin (0.03 IU/ml) or 3% mepivacaine without vasoconstritor 8 . Few respondents reported have been considering the toxicity of local anesthetic or vasoconstrictor for the choice of anesthetic solution; however, anesthetic solutions with higher toxic effects were not mentioned (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Excess of VCs may also cause systemic side effects associated with the stimulation of adrenergic receptors, including elevated systolic blood pressure and heart rate, and from simple palpitations to more serious cardiac arrhythmias. Cerebral hemorrhage can occur in dramatic increases in blood pressure or in patients with weakened vascular walls 8 . Besides patients with cardiovascular disease, those with uncontrolled diabetes may present some problems due to the stimulation of gluconeogenesis and glycogenolysis by these drugs 9 .…”
Section: Dentists' Knowledge Regarding Signs and Symptoms Of The Systmentioning
confidence: 99%
“…17 In dental practice, the use of anesthetics with epinephrine at 1:100,000 corresponds to a dose of 0.018 mg, a dose well below the 0.5 to 1 mg administered in the treatment of anaphylaxis or a heart attack. 18 Recent studies, which compared the use of anesthetics with and without epinephrine in hypertensives and nonhypertensives during dental extractions, showed statistically significant changes in neither blood pressure nor heart rate between the groups. 9,15 Certain authors have compared changes in blood pressure in hypertensive and nonhypertensive patients while using different anesthetic agents, without any relevant results.…”
Section: Discussionmentioning
confidence: 99%